Modeling the impacts of sand placement strategies on barrier island evolution in a semi-enclosed bay system - Davina L. Passeri; Rangley C. Mickey; David M. Thompson; Michael Itzkin; Elizabeth Godsey; Matthew V. Bilskie; Alexander Seymour; Autumn Poisson; Jin Ikeda; Scott C. Hagen (Coastal Engineering, 2025)

Modeling the effects of large-scale interior headland restoration on tidal hydrodynamics and salinity transport in an open coast, marine-dominant estuary - Davina L. Passeri; Robert L. Jenkins; Autumn Poisson; Matthew V. Bilskie; Peter Bacopoulos (Frontiers in Marine Science, 2023)
The effects of large-scale interior headland restoration on tidal hydrodynamics and salinity transport in an open coast, marine dominant estuary (Grand Bay, Alabama, U.S.A) are investigated using a two-dimensional model, the Discontinuous-Galerkin Shallow Water Equations Model (DG-SWEM). Three restoration alternatives are simulated for present-day conditions, as well as under 0.5 m of sea level rise (SLR). Model results show that the restoration alternatives have no impact on tidal range within the estuary but change maximum tidal velocities by ±5 cm/s in the present-day scenarios and by ±7 cm/s in the scenarios with 0.5 m of SLR. Differences in average salinity concentrations for simulated tropical and frontal seasons show increases and decreases on the order of 2 pss in the embayments surrounding the restoration alternatives; differences were larger (on the order of ±4 pss) for the scenarios with 0.5 m of SLR. There were minimal changes in average salinity outside of the estuary and no changes offshore. The size and position of the alternatives played a role in the salinity response as a result of changing the estuarine shoreline geometry and affecting the fetch within the bay. SLR was more impactful in increasing exposure to low salinity values (i.e., less than 5 pss) than the presence of the restoration alternatives. Overall, the modeled results indicate that these large-scale restoration actions have limited and localized impacts on the hydrodynamics and salinity patterns in this open coast estuary. The results also demonstrate the nonlinear response of salinity to SLR, with increases and decreases in the maximum, mean and minimum daily salinity concentrations from present-day conditions. This nonlinear response was a result of changes in the directions of the residual currents, which affected salinity transport.

Taking a macroscale perspective to improve understanding of shallow lake total phosphorus and chlorophyll a - Kendra Spence Cheruvelil; Katherine E. Webster; Katelyn B. S. King; Autumn C. Poisson; Tyler Wagner (Hydrobiologia, 2022)